2014
DOI: 10.4321/s1130-01082014000100006
|View full text |Cite
|
Sign up to set email alerts
|

Indications of capsule endoscopy in Crohn's disease

Abstract: Capsule endoscopy currently plays a relevant role for Crohn's disease. This manuscript will discuss the current indications and practical uses of capsule endoscopy in this disease. It is a non-invasive technique that represents a significant advance in the endoscopic diagnosis of small bowel conditions. These circumstances, together with its diagnostic yield and excellent tolerability, make it considerably acceptable by both patients and physicians. This paper discusses the current evidence on the specific cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(95 reference statements)
0
4
0
2
Order By: Relevance
“…In a study published in 2012, the authors showed that patients with these suspicion criteria were in fact more likely to present inflammatory lesions in CE, but they also reported that individuals with three or more of these criteria were at a significantly higher risk than those with only one or two of them (25). Based on these results in some systematic reviews about the role of CE in IBD, authors have indicated that the greater number of criteria a patient has, the higher the suspicion of CD should be, no matter which of the criteria are present (26,27). But it has not been completely analyzed if any of these criteria (or association of criteria) could be superior to the rest.…”
Section: Discussionmentioning
confidence: 95%
“…In a study published in 2012, the authors showed that patients with these suspicion criteria were in fact more likely to present inflammatory lesions in CE, but they also reported that individuals with three or more of these criteria were at a significantly higher risk than those with only one or two of them (25). Based on these results in some systematic reviews about the role of CE in IBD, authors have indicated that the greater number of criteria a patient has, the higher the suspicion of CD should be, no matter which of the criteria are present (26,27). But it has not been completely analyzed if any of these criteria (or association of criteria) could be superior to the rest.…”
Section: Discussionmentioning
confidence: 95%
“… 5 23 At the time of initial diagnosis, two-thirds of CD cases involve the SB, and up to one-third of patients have lesions limited to the SB. 24 25 As symptoms are usually nonspecific, the location of lesions in CD is very difficult to ascertain clinically. On diagnosing CD, it is important to ascertain the involvement of the SB and to evaluate and characterize any existing SB lesions.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, CE findings resulted in altered management plans for 90% of patients with sCD and 73% of patients with eCD. 25 However, another study reported that a change in treatment was recommended in 52.3% of patients on the basis of CE findings. 8 In the present study, we found that therapeutic strategies for 70.2% of patients in the sCD group were modified on the basis of CE findings; in the eCD group, 57.1% of patients continued current medications or had a specific medication added.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative is capsule endoscopy (CE), a non-invasive and well tolerated technique, with a crucial role in three settings: in suspected CD, unclassified IBD (IBDU) and established CD. 39 It can be useful in establishing diagnosis, assessing severity and disease extension.…”
Section: Endoscopic Monitoringmentioning
confidence: 99%